Papua New Guinea : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Papua New Guinea. (IMF Staff Country Reports; Country Report ;, 2009)
This 2008 Article IV Consultation highlights that GDP per capita for Papua New Guinea remains low. An unattractive investment environment, primarily owing to weak infrastructure, problems with governance, and high crime curtails development. Executive Directors have commended the authorities for saving the bulk of recent windfall mineral revenues and repaying public debt to improve the external debt position. They have also acknowledged the authorities' policy of slowing exchange rate depreciation to moderate inflationary pressures.